Penerapan Model Ragambasi Berdasarkan Tingkat Kemampuan Awal Siswa pada Pelajaran Matematika - Sri Rahmawati; Erwin Nurdiansyah (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Application of a Ragambation Model Based on a Student's Initial Ability Level in a Mathematics Lesson. This study aims to determine students' understanding before and after the application of the Ragambasi Model and find out the improvement in students' mathematical understanding after the application of the Ragambasi Model. This research is a pre-experimental design research with One-Group Pretest-Posttes Design. The study population was all students of class VIII MTsN 3 Bulukumba which amounted to 104 students divided into 3 classes. The sample is taken randomly or randomly because it consists of 3 classes. The sample in this study was class VIIIA MTsN 3 Bulukumba students consisting of 35 students. The instruments used by the authors in this study were student learning outcomes tests and observation sheets. The data processing carried out by the author in this case is to use descriptive statistical analysis and inferential statistics. The results showed that: 1) the average results of learning mathematics before the application of the Ragambasi Model were in the moderate category. 2) The average learning outcomes of mathematics after the application of the Ragambasi Model are in the high category. Based on the results of inferential analysis, it shows that there is a significant improvement in the application of the Ragambasi Model based on the level of students' initial ability in mathematics.